MiR-1-3p Inhibits Lung Adenocarcinoma Cell Tumorigenesis via Targeting Protein Regulator of Cytokinesis 1 - Li, Tao; Wang, Xiuxiu; Jing, Lijun; Li, Yu (Frontiers in Oncology, 2019)
Lung adenocarcinoma (LUAD) is one of the most lethal malignancies, posing a threat to human health. However, the molecular mechanisms underlying LUAD development remain largely unknown. In this study, we found that miR-1-3p was significantly downregulated in human LUAD tissues and cell lines and played an inhibitory role in LUAD cell tumorigenesis, as evidenced by the significantly reduced proliferation, migration, and invasion of LUAD cells in response to miR-1-3p overexpression. Mechanistically, miR-1-3p physically interacted with the 3ʹ-untranslated region (UTR) of protein regulator of cytokinesis 1 (PRC1) mRNA, leading to downregulation of PRC1. Overexpression of PRC1 reversed the inhibitory effects of miR-1-3p on LUAD cell tumorigenesis, suggesting that the miR-1-3p/PRC1 axis is majorly involved in suppressing LUAD development and progression. Consistently, PRC1 was dramatically induced in LUAD tissues and cell lines as well as associated with a poor prognosis in LUAD patients. Taken together, our study identified the miR-1-3p/PRC1 axis as an important regulatory mechanism contributing to LUAD inhibition and provided valuable clues for the future development of therapeutic strategies against LUAD.